Ramazzottius thulini (Pilato, 1970) bona species and description of Ramazzottius libycus sp. nov. (Eutardigrada, Ramazzottidae) - Pilato, Giovanni; D’urso, Vera; Lisi, Oscar (Zootaxa, 2013)
Comparing the type series of Ramazzottius thulini with specimens of Ramazzottius oberhaeuseri, from the locus typicus, we confirmed there are morphological and metric differences between these two species. This evidence convinced us that R. thulini should be considered a bona species. A new species, Ramazzottius libycus sp. nov., is also described. Ramaz-zottius libycus sp. nov. differs from R. oberhaeuseri in having more slender internal claws I–III and anterior claws IV, and other metric differences relative to all claws. The new species differs from R. thulini in details of the cuticular ornamen-tation, stylet supports inserted on the buccal tube in a slightly more caudal position, internal claws slightly different in shape, and some metric differences relative to all claws. It appears R. thulini and R. libycus sp. nov. are sibling species of R. oberhaeuseri and therefore the authors expect that there are other cryptic species included under the R. oberhaeuseri name still awaiting to be recognized and described.